2011
DOI: 10.1140/epjb/e2011-20670-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic studies of the two dimensional Falicov-Kimball model on a triangular lattice

Abstract: Thermodynamic properties of the spinless Falicov-Kimball model are studied on a triangular lattice using numerical diagonalization technique with Monte-Carlo simulation algorithm. Discontinuous metal-insulator transition is observed at finite temperature. Unlike the case of square lattice, here we observe that the finite temperature effect is not able to smear out the discontinuous metal-insulator transition seen in the ground state. Calculation of specific heat (Cv) shows single and double peak structures for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The triangular lattice is geometrically frustrated; thus, the regular charge ordering as the one in the square lattice does not occur at low temperatures. [28][29][30][31] Instead, striped or bounded phases are formed. [28][29][30][31] However, one might expect that the next-nearest-neighbor hopping t 2 is always smaller than the nearest-neighbor hopping t, and for small values of t 2 the frustrations of the individual sublattices do not break the bipartite structure of the whole honeycomb lattice.…”
Section: The Haldane Model With Local Interactionmentioning
confidence: 99%
“…The triangular lattice is geometrically frustrated; thus, the regular charge ordering as the one in the square lattice does not occur at low temperatures. [28][29][30][31] Instead, striped or bounded phases are formed. [28][29][30][31] However, one might expect that the next-nearest-neighbor hopping t 2 is always smaller than the nearest-neighbor hopping t, and for small values of t 2 the frustrations of the individual sublattices do not break the bipartite structure of the whole honeycomb lattice.…”
Section: The Haldane Model With Local Interactionmentioning
confidence: 99%
“…The eigenvalue spectrum of the FKM Hamiltonian is obtained by numerical diagonalization technique on a finite-size triangular lattice with periodic boundary conditions (PBC). In order to calculate the average values of the physical quantities the classical Monte-Carlo simulation algorithm is employed by 'annealing' over a subset of configurations of the 'classical' variables {ω iσ = f † iσ f iσ } [5,6,7,8].…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that these systems may very well be described by different variants of the Falicov-Kimball model (FKM) [15,16,23,24,25,26,27,11] on the triangular lattice. The FKM (having two kinds of states namely itinerant states and localized states) was originally introduced to study the metal-insulator transition in the rare-earth and transition-metal compounds [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Many numerical and exact calculations are available for the different extensions of spinless FKM on the bipartite and non-bipatatite lattices in the absence of magnetic field and taking into account interactions between itinerant and localized electrons [30,31,23,24,25,26]. These results show many novel phenomenon like charge and orbital ordering and metal-insulator transition as a function of electron correlations and filling of the electrons.…”
Section: Introductionmentioning
confidence: 99%